Menanamkan Literasi Lingkungan pada Peserta Didik Sekolah Dasar Melalui Spesific Program : Eco-Mapping - Prihanta, Wahyu; Purwanti, Elly; Muizzudin, Muizzudin; Cahyono, Eko (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
Elementary school students are a period for children's development to acquire the educational process by applying a real learning approach based on facts and not much theory. Elementary school age has an important meaning for children's development, because it is a pillar of support for the solid development of personality, psychomotor, cognitive, and social, including preparing their sensitivity to environmental problems in order to increase the environmental literacy of students. For this reason, it is necessary to develop a learning environment that is in accordance with the characteristics of elementary school students, with the following characteristics: 1) environmental learning that instills environmental-loving behavior; 2) learning environment that intensifies the interaction of students and learning resources; 3) environmental learning is done while playing; 4) learning for the development of the potential of students; 5) learning environment that provides a sense of security to students; 6) environmental learning carried out in an integrated manner; 7) environmental learning that involves community participation; and 8) environment-based thematic learning. The purpose of this activity is to increase the environmental literacy of students through concrete actions of habituation of environmentally friendly and sustainable behavior in order to overcome environmental problems in schools and surrounding communities, including preparing their sensitivity to environmental problems in order to increase students' environmental literacy. Implementation of activities in the form of school environmental audits, through eco-mapping activities of the school environment. Audits conducted by students include: 1) electrical energy; 2) garbage; 3) water sources; 4) noise; and 5) green environment. The results of school environmental audit activities using the eco-mapping method, audits on the parameters of energy sources, waste, water, and the school's green environment, it was found that from all the observed parameters, schools had not utilized environmental resources optimally. Knowledge, awareness, and behavior towards the environment among students at the elementary school level are still quite low.